The Implementation of Anti-Corruption Education Models in Pesantren - Mohammad Takdir; Mohammad Hosnan; Nuzulul Khair; Paisun (EL-TARBAWI, 2022)
Corruption is an extraordinary crime in Indonesia that is contrary to the values of religious education. This study aims to explore anti-corruption education models based on religious ethics which are implemented in the pesantren of Annuqayah, Guluk-Guluk Sumenep. This study analyzes the roles of the pesantren of Annuqayah in building anti-corruption characters in students from an early age. The research was conducted at the pesantren of Annuqayah which is one of the oldest Islamic boarding schools in Madura. The study uses a qualitative method to elaborate anti-corruption education models based on religious ethics at the pesantren of Annuqayah, Guluk-Guluk Sumenep, Madura. Researchers used observation, interviews, and documentation in collecting research data. The study found that the anti-corruption education models applied in the pesantren of Annuqayah are role models, habituation of behavior, integration between subjects and behavior, and models of rewards and punishments. Meanwhile, the roles of Annuqayah pesantren in shaping the students’ anti-corruption character are building values of Aswaja (Ahlus-Sunnah wal-Jama’ah), establishing an honest canteen, giving trust to manage pesantren finances, and providing rewards and punishments. The research is valuable as feedback for the government in the field of education in its efforts to fight corruption in Indonesia.